Phosphorus, phosphorous, and phosphate. Issue 4 (20th December 2012) - Iheagwara, O. Susan; Ing, Todd S.; Kjellstrand, Carl M.; Lew, Susie Q.
Abstract: This article distinguishes the terms "phosphorus, phosphorous, and phosphate" which are frequently used interchangeably. We point out the difference between phosphorus and phosphate, with an emphasis on the unit of measure. Expressing a value without the proper name or unit of measure may lead to misunderstanding and erroneous conclusions. We indicate why phosphate must be expressed as milligrams per deciliter or millimoles per liter and not as milliequivalents per liter. Therefore, we elucidate the distinction among the terms "phosphorus, phosphorous, and phosphate" and the importance of saying precisely what one really means.